Structural Conceptual Framework of Supply Chain Process for Lean Healthcare Practices and Healthcare Performance - Habidin, Nurul Fadly; Rosdi, Siti Asma’ Mohd; Zainol, Zuraidah; Shaharudin, Mohd Rizaimy; Mohd Fuzi, Nursyazwani; Abdul Rashid, Nurulizwa; Ong, Sharon Yong Yee (ExcelingTech, 2020)
The purpose of this study is to review the supply chain process of lean healthcare practices (LHP). LHP consists of leadership, employee engagement, customer engagement, continuous improvement, just in time, lean production, and workflow processes had been identified. For this research purpose, questionnaires will be distributed in selected hospitals by the researcher. For implications, this finding would provide good material as guideline and references to manufacturing industry especially to Malaysian healthcare firm, Malaysian government hospital, lean healthcare consultants, and local and international academics. Thus, LHP tools are important to improve healthcare performance in the Malaysian healthcare industry. The paper contributes to supply chain management literature by identifying LHP in the Malaysian healthcare industry.